Primary health care services for obesity and hypertension in sub-urban community: focus on nutrition - Peter, Malachy B.; Peters, Esegbue; Nwose, Ezekiel; Ofili, Charles (International Journal of Advances in Medicine, 2023)
Medical nutrition therapy (MNT) is a major clinical care concept, especially for non-communicable diseases such as obesity and hypertension. Primary healthcare (PHC) centers are the first point of contact with health services and provide a point of entry for the entire health system. Research has revealed that access to primary healthcare services is associated with improved health outcomes, such as an improvement in self-rated health and a decline in all-cause mortality. However, the integration of MNT in hypertension and obesity management at PHC level is unclear. The aim of this study is to establish PHC services for obese and hypertensive individuals with a focus on nutrition, and the need for further research. Awareness of dietary approach to stop hypertension (DASH) among health workers, obese and hypertensive individuals and it utilization in practice was low in PHC centers this is due to lack of registered dietitians’ nutritionists who are trained in MNT which is complicated by lack of ministerial funding of PHC facilities.